Analyzing the 8th Grade Students’ Mastery of Verb Tenses in English Grammar at SMP Angkasa Lanud Sutan Sjahrir Padang - Zulfadli Zulfadli; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2023)
This research intends to identify the eighth grade students’ mastery of verb tenses in simple present, simple past, and present continuous and the factors that contributed to the eighth grade success or failure in mastering the verb tenses at SMP Angkasa Lanud Sutan Sjahrir Padang. This research used mixed-method research design where interview and grammar test about verb tenses were applied to collect the data. The finding showed that most of the students’ mastery of verb tenses were categorized as failing. that teaching methods and materials, motivation, lack of exposure to English outside the classroom, and students’ language background considered as the main factors that contributed to students’ failure in mastering verb tenses. On the other hand, the key factors that contributed to students’ success in mastering verb tenses can be seen on the students’ much exposure to English outside the classroom, motivation, assessment, and students’ language background which have learned English earlier than the others. This research is expected to English language teaching and learning process in SMP Angkasa Lanud Sutan Sjahrir Padang.